SUV39H2 promotes colorectal cancer proliferation and metastasis via tri-methylation of the SLIT1 promoter. (28th May 2018) - Shuai, Wendi; Wu, Jiangxue; Chen, Shuai; Liu, Ranyi; Ye, Zhihua; Kuang, Chunmei; Fu, Xiang; Wang, Gaoyuan; Li, Yingchang; Peng, Qihua; Shi, Wei; Li, Yizhuo; et al.
Abstract: Suppressor of variegation 3–9 homolog 2 (SUV39H2) is a member of the SUV39H subfamily of lysine methyltransferases. Its role in colorectal cancer (CRC) proliferation and metastasis has remained unexplored. Here, we determined that SUV39H2 was upregulated in CRC tissues compared with that in adjacent non-neoplastic tissues. Further statistical analysis revealed that high SUV39H2 expression was strongly associated with distant metastasis (P = 0.016) and TNM stage (P = 0.038) and predicted a shorter overall survival (OS; P = 0.018) and progression-free survival (PFS; P = 0.018) time for CRC patients. Both in vitro and in vivo assays demonstrated that ectopically expressed SUV39H2 enhanced CRC proliferation and metastasis, while SUV39H2 knockdown inhibited CRC proliferation and metastasis. A molecular screen of SUV39H2 targets found that SUV39H2 negatively regulated the expression of SLIT guidance ligand 1 (SLIT1). Moreover, rescue assays suggested that SLIT1 could antagonize the function of SUV39H2 in CRC. Mechanistic studies indicated that SUV39H2 can directly bind to the SLIT1 promoter, suppressing SLIT1 transcription by catalyzing histone H3 lysine 9 (H3K9) tri-methylation. In summary, we propose that SUV39H2 can predict CRC patient prognosis and stimulate CRC malignant phenotypes via SLIT1 promoter tri-methylation. Highlights: SUV39H2 is a novel prognostic factor of CRC. SUV39H2 enhances CRC proliferation and metastasis both in vitro and in vivo. SLIT1 is a critical downstream target of SUV39H2. SUV39H2 directly binds to SLIT1 promoter and catalyzes H3K9 tri-methylation to inhibit SLIT1 transcription.